Corn grains losses in the function of different speeds of the harvesting - E. Neves; B. S. Oliveira; W. D. A. Oliveira (Scientific Electronic Archives, 2020)
The main objective of this work was to quantify and evaluate the occurrence of corn grain losses due to the different speeds of the harvesting machine in the second harvest, considering that, in the state of Mato Grosso, corn cultivation, mainly in the off-season, has been gaining space every year due to the increase in both the quality and the quantity of grains planted and harvested in the state. The frame was made in relation to the size of the platform with 0.37 m in length, the frame was superimposed on the straw to collect the grains lost by the harvester. The experiment was carried out at speeds of 3.5; 4,5; 5.0; 5.5 and 6 km.h-1 with rotation of 540 per minute in the cylinder and concave in the opening position No. 05 corresponding to 50 mm of standardized opening for all speeds, where it was possible to observe that there were no significant losses of corn kernels with the speed of the harvester 3.5 km.h-1. The variation between the losses is 30.2 kg per hectare of whole corn grains, between the speeds of harvest tested. It was concluded that the speed of the harvester of 3.5 km.h-1 has lower losses of corn kernels when compared to the other speeds experienced, noting that this loss was lower, acceptable for maize.